Effectiveness of Reserve Requirement Policy in the Dual Banking System During COVID-19 - Al Banna, Hasan; Munandar, Aris; Mutmainah, Lu'liyatul (Jurnal Ilmu Ekonomi Terapan, 2025)
Objective: This study assesses the effectiveness of the reserve requirement (RRR) as part of a quantitative easing (QE) package within the dual banking system during the COVID-19 shock. The core question is whether changes in the RRR stimulate lending/financing, with a specific focus on differential responses between Islamic and conventional commercial banks. Design/Methods/Approach: Using macro-level industry data covering conventional and Islamic commercial banks from 2015 to March 2020, the analysis applies an Autoregressive Distributed Lag (ARDL) bounds testing framework to identify short- and long-run relationships between monetary policy and lending/financing. ARDL is used for this study because of its ability to capture adjustment dynamics that may differ across the two banking pillars under a QE regime. Findings: The results indicate that Islamic banks are more sensitive to the RRR policy than their conventional counterparts; lowering the RRR effectively promotes financing in Islamic commercial banks. Conventional bank lending appears less responsive to monetary transmission via interest rates, whereas Islamic bank financing is more reactive to policy changes. These patterns support the case for unconventional monetary tools to reinforce transmission, given the dominance of conventional banks in the financial system. Originality/Value: The study contributes by jointly identifying the impact of the RRR across both pillars of a dual banking system within a COVID-era QE context, offering ARDL-based evidence of asymmetric sensitivity between Islamic and conventional banks. Practical/Policy implication: The study contributes by jointly identifying the impact of the RRR across both pillars of a dual banking system within a COVID-era QE context, offering ARDL-based evidence of asymmetric sensitivity between Islamic and conventional banks.